Endometrial Changes in Surgical Specimens of Perimenopausal Patients Treated With Ulipristal Acetate for Uterine Leiomyomas. (November 2018) - Nogales, Francisco F.; Crespo-Lora, Vicente; Cruz-Viruel, Nelly; Chamorro-Santos, Clara; Bergeron, Christine
Abstract : Ulipristal acetate (UPA) is used to treat leiomyomas, and its effect on the endometrium has been studied in biopsy material. Reversible histologic modifications were found, named progesterone receptor modulators–associated endometrial changes (PAEC). However, hysterectomies from patients treated with UPA have not been analyzed. For the first time, we examined surgical specimens from 100 leiomyoma-treated patients for UPA-related endometrial changes. We analyzed the distribution of lesions, involution after treatment, and the relationship between type and extent of lesions and dosage. Clinically, 72 patients were treated with 1 cycle of UPA; 23 patients with 2 cycles, and 5 with 3 cycles. A total of 66 patients underwent surgery in the first 4 wk after treatment, 24 were operated between 5 and 12 wk after discontinuation of UPA, and 10 after more than 12 wk after the last cycle, up to a maximum of 32 wk. Histologically normal endometria were found in 41 cases and PAEC in 59 cases. PAEC consisted of irregular, cystic glands showing a flattened secretory-like epithelium with vacuolation, coexisting mitoses and apoptosis, and were found focally within cyclic endometria in 51 cases. Only in 8 cases did diffuse PAEC involve the whole endometrium, transforming it into a thick spongy cushion. PAEC also occurred in adenomyosis. There was no relationship between dosage and type and extent of lesions. Diffuse PAEC, which usually presents differential diagnoses with hyperplasia, occurred in only 8 cases, being only present during the first 4 wk after discontinuation of treatment and was independent of the number of cycles administered.